Lethal Provocation : The Constantine Murders and the Politics of French Algeria - Cole, Joshua, 1961- (Book collections on Project MUSE., 2019)
"Explores the most lethal episode of anti-Jewish violence to happen on French territory in peacetime in the twentieth century, a riot in Constantine, Algeria in 1934 in which 28 people died"--